Feasibility analysis of a pipeline integrity management plan for oil and gas industry in developing countries : the case of niger delta (nigeria) oil spills - Njoku, William Chibuzor (2019)
Coordenação de Aperfeiçoamento de Pessoal de Nivel Superior